The role of apoptotic factors in Sindbis virus infection and replication in the mosquito vector Aedes aegypti - O'Neill, Katelyn Leigh (Kansas State University, 2013)
Mosquitoes are carriers of a variety of harmful human pathogens, including viruses. In order to be successfully transmitted, a virus must evade mosquito immune responses. In this work, the innate immune role of apoptosis in mosquito-virus interactions was examined utilizing the disease vector Aedes aegypti and Sindbis virus. Ae. aegypti is the main vector for yellow fever and dengue virus, which result in over 100 million infections per year. Sindbis virus (Togaviridae) can be transmitted to vertebrates by Ae. aegypti in the laboratory. Sindbis is also well characterized molecularly, making it a good model system for understanding virus-vector interactions. Sindbis MRE-16 recombinant virus clones were utilized to express either an antiapoptotic or pro-apoptotic gene during virus replication. Mosquitoes were infected with recombinant virus clones during a blood meal or by intrathoracic injection. Midgut tissue and whole body samples were analyzed for virus infection and dissemination. Virus was also quantified in saliva and mosquito survival was assayed. Decreased infection in the midgut and delayed virus replication were observed in mosquitoes that were infected with virus expressing a pro-apoptotic gene. Infection with this virus clone also resulted in less virus in the saliva and reduced survival of infected mosquitoes. In addition, negative selection against pro-apoptotic gene expression during virus replication was observed. Collectively, these data suggest that apoptosis can serve as an antiviral defense in Ae. aegypti and may potentially be exploited to control virus transmission. An additional study included in this dissertation focused on zebrafish development and migration of somitic precursors from the tailbud. The tailbud consists of a population of stem cells at the posterior tip of the embryonic tail. The exit of these stem cells from the tailbud is required for the formation of tail somites. A novel double mutant was identified that lacked the t-box transcription factor spadetail and the BMP inhibitor chordin. Double mutants completely lacked somites and had an enlarged tailbud due to accumulation of stem cells that were unable to exit the tailbud. This study indicates the importance of BMP inhibition and spadetail expression in the proper exit of muscle precursors from the tailbud.
Keywords: Sindbis; Aedes aegypti; Apoptosis; Zebrafish; Tailbud; Developmental Biology (0758); Molecular Biology (0307); Virology (0720)